Relation-theoretic metrical coincidence theorems under weak C-contractions and K-contractions - Faruk Sk; Asik Hossain; Qamrul Haq Khan (AIMS Mathematics, 2021)
In this paper, we prove some coincidence point theorems for weak C-contractions and K-contractions involving a new auxiliary function in a metric space endowed with a locally f-transitive binary relation. In this context, we generalize some relevant fixed point results in the literature. Further, we give an example to substantiate the utility of our results.